Contractual documentation in project finance and the need for connectivity (2021)
Project finance cannot be done in Isolation. It draws a series of participants to the projects and, therefore, culminates into different types of agreement reached by Investors or parties. The agreements are geared at serving series of purposes, such as bankability, risk control mechanisms, guarantees in relation to the projects, and offering a medium of privity of contract for other parties who ordinarily would not have been privy to the agreements. The parties to project finance will require that their relationship be memorialised and specified. There are series of connected agreements which will be documented and may be linked to the main financing agreement by the parties. These agreements tend to define the obligations of the participants, their roles in the venture, and the allocation of risks. The agreements which are negotiated are required, forming part of the documentation in a project finance. These agreements specify the roles of the parties and the relationship or link to the project. This article examines the roles of these agreement, clearly stating their impacts and contribution to project finance. It makes a case for the coordination of the complexities stemming from the agreements to avoid extemporaneous effects that can jeopardise the essence of a project finance scheme.